Medición de canales de difusión en la Universidad Cooperativa de Colombia - sede Medellín. (2018)
This research project focused on conducting a measurement pilot of the internal broadcasting channels of the Universidad Cooperativa de Colombia - Medellin, in order to know with certainty if the internal communication was efficient and which of all the media is the one generated greater interest in the university community. This with the objective of meeting a need found within the university, knowing that there was no record of a measurement of internal channels. From the hand of the current communicator, Margarita Serna Uribe, it was decided to create the diagnosis using the Google Survey tool, where through quantitative and qualitative questions, it was possible to decipher, thanks to the samples, the effectiveness of internal communication and which of all communication channels was preferred by students, teachers and administrators of the Universidad Cooperativa de Colombia - Medellín.